2014
DOI: 10.1039/c4cp00597j
|View full text |Cite
|
Sign up to set email alerts
|

Size-selected gold clusters on porous titania as the most “gold-efficient” heterogeneous catalysts

Abstract: Research on homogeneous and heterogeneous catalysis is indeed convergent and finds subnanometric particles to be at the heart of catalytically active species. Here, monodisperse gold clusters are deposited from the gas phase onto porous titania generating well-defined model systems and the resulting composite materials exhibit a sharp size-dependency on the number of gold atoms per cluster and exceptionally high-turnovers toward the bromination of 1,4-dimethoxybenzene are observed. This indicates that the deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Another approach is based on the soft deposition of well-defined metal clusters, prepared and mass-separated in the gas phase 11 . However, even though subnanometer dimensions can be achieved, the method is usually limited to low particle coverages in order to avoid cluster aggregation, and deposition onto non-planar high surface area supports remains challenging 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Another approach is based on the soft deposition of well-defined metal clusters, prepared and mass-separated in the gas phase 11 . However, even though subnanometer dimensions can be achieved, the method is usually limited to low particle coverages in order to avoid cluster aggregation, and deposition onto non-planar high surface area supports remains challenging 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier publication we studied multilayer films of Molybdenum clusters soft landed on HOPG [16]. The samples have been analyzed in-situ using an ultrahigh vacuum scanning tunneling microscope.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental set-up has been described in detail elsewhere [15,16]. In short, W n À cluster anions are generated in a magnetron cluster source.…”
Section: Methodsmentioning
confidence: 99%
“…Yet studies in the late 80s showed that Au nanoparticles supported on metal oxides such as TiO 2 exhibits an extraordinary high activity towards various catalytic oxidation and reduction reactions, such as low-temperature combustion, partial oxidation of hydrocarbons, hydrogenation of unsaturated hydrocarbons, and reduction of nitrogen oxides. [1][2][3][4][5][6][7][8][9][10] The catalytic properties of Au nanoparticles originate from quantum, electronic, and geometric finite-size effects, and are therefore strongly related to the particle size. 3,11 For example, Au nanoparticles supported on TiO 2 exhibit a high activity towards the oxidation of CO only when their size is within an optimal range of 2-3 nm.…”
Section: Introductionmentioning
confidence: 99%